Can artificial ecological corridors be used for ecological restoration of cultivated land in Chinese Mollisols? - Xu, HuiBo; Wu, SongTao; Diehl, Jessica Ann (Frontiers in Plant Science, 2022)
Artisficial ecological corridors (AECs) are internationally recognized as a standard method for restoring the regional ecological environment. However, the coupling relationship between AECs and soil quality has rarely been studied. Harbin, a typical mollisols region in the cold area of China, has severe soil problems and remediation is urgently needed, yet AEC research in this region is lacking. Based on the perspective of soil restoration, the construction factors of ecological corridors are quantitatively evaluated. It can predict the long-term impact of AECs already built along Harbin’s Ashi River on soil chemical indices. This research studied the ecological restoration of secondary woodland, cultivated land within the ecological corridor, and cultivated land outside the influence range of the corridor under the influence of continuous recovery time and different locations in the corridor (distance from the Ashe River). Soil samples were taken from 5 plots, with a total of 161 samples, and 12 indices of soil ecological characteristics were monitored. The result are as follows: It is believed that the quality restoration of mollisols through ecological corridors has great application potential. Based on the low-cost natural restoration of ecological corridors, the highest values of total phosphorus (TP) and soil organic matter (SOM) in soil indices were detected in corridors (restored for more than 10 years). In addition, after ten years of recovery, pH and electrical conductivity (EC) in the ecological corridor returned to normal from high levels in cultivated land that far exceeded the reference values. The recovery process of mollisols mass begins to decrease, then increases, and finally reaches and exceeds the reference value of standard mollisols. The redundancy analysis of soil samples found the distance to be a key factor affecting soil total nitrogen (TN), SOM, and cation exchange capacity (CEC). Recovery time is a crucial factor affecting soil total organic carbon (SOC), pH and EC. According to the TN, SOM, and CEC mollisols indices, the ecological corridor’s unilateral width is 125-150m. According to the SOC, pH, and EC indices of mollisols, the AECs should complete a natural recovery cycle of a minimum of 13 years. This study reveals the change mechanism of soil quality in mollisols area corridors based on recovery time and location. This research offer ideas and a scientific basis for worldwide governments in mollisols to formulate mollisols restoration policies.